The implications of library 2.0 tools in Malaysian academic libraries towards reference services / Rafidah Abdul Aziz, Zuraidah Arif, Ruzita Ramly... [et.al]. - Abdul Aziz, Rafidah; Arif, Zuraidah; Ramly, Ruzita; Abdullah (Hj), Che Zainab; Husaini, Haslinda (2011)
A library 2.0 application is an adaptation of Web 2.0 into a library environment to strategically adopt new technology in enhancing the role of libraries. Usage of Library 2.0 tools is just recently present in Malaysian academic libraries. In this paper, the authors attempt to study the implications of implementing Library 2.0 in Malaysian academic libraries. The study is about the implications brought on by e Library 2.0 in Malaysian academic libraries. The purpose of this research is to identify the current trends of the Library 2.0 tools in Malaysian academic libraries towards reference services. The paper attempts to determine the use and the implications of Library 2.0 in reference services in the Malaysian academic libraries. The study covers six research questions including, Which academic libraries fully utilized Library 2.0 tools?, Which Library 2.0 tools are highly used by the academic libraries in Malaysia?, What is the usage statistics of Library 2.0 tools?, What are the implications of Library 2.0 tools in the Malaysian academic libraries?, Which Library 2.0 tools are appropriate for reference services in the Malaysian academic libraries?, and How does Library 2.0 tools assist reference services?.The study used the qualitative method whereby the research performed two approaches: website observation of 15 Malaysian academic library websites and semi-structured interview with five librarians from different academic libraries. The results indicated that Facebook is the most popular with 9 of 15 academic libraries in Malaysia had used this application. Most of the academic libraries used Library 2.0 for the purpose of increasing the interaction with library users in informal ways. Findings from the research are useful for librarians and researchers in studying the usage of Library 2.0 in Malaysia and the benefits gained by the libraries.